2019
DOI: 10.1096/fj.201901331r
|View full text |Cite
|
Sign up to set email alerts
|

Mettl17, a regulator of mitochondrial ribosomal RNA modifications, is required for the translation of mitochondrial coding genes

Abstract: Embryonic stem cells (ESCs) are pluripotent stem cells with the ability to self‐renew and to differentiate into any cell types of the 3 germ layers. Recent studies have demonstrated that there is a strong connection between mitochondrial function and pluripotency. Here, we report that methyltransferase like (Mettl) 17, identified from the clustered regularly interspaced short palindromic repeats knockout screen, is required for proper differentiation of mouse embryonic stem cells (mESCs). Mettl17 is located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 53 publications
2
43
0
3
Order By: Relevance
“…Furthermore, the enzymatically inactive METTL15 can partially restore the m 5 C841 methylation decreased in METTL15-null cells, raising the question of whether the crosstalk is mediated by physical interactions between METTL15 and the m 5 C methyltransferase, NSUN4. Undoubtedly, the investigation of how modifications of mt-rRNA are coordinately deposited in an orderly manner will significantly increase our understanding of mitoribosome maturation (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the enzymatically inactive METTL15 can partially restore the m 5 C841 methylation decreased in METTL15-null cells, raising the question of whether the crosstalk is mediated by physical interactions between METTL15 and the m 5 C methyltransferase, NSUN4. Undoubtedly, the investigation of how modifications of mt-rRNA are coordinately deposited in an orderly manner will significantly increase our understanding of mitoribosome maturation (31) .…”
Section: Discussionmentioning
confidence: 99%
“…METTL17 localizes to mitochondria and associates with the mt-SSU. Loss of METTL17 leads to around 70% reduction of m 4 C840 and 50% reduction of m 5 C842 of 12S mt-rRNA, severely compromising integrity of the mt-SSU and mitochondrial protein translation (Shi et al, 2019). Collectively, these data suggest an important role for METTL17 in mitochondrial function, although further work is needed to assess potential interdependence of METTL15 and METTL17 in m 4 C839 methylation.…”
Section: Mettl15 (M 4 C839)mentioning
confidence: 94%
“…Interestingly, Shi et al have recently identified another member of the METTL family, METTL17, to modulate m 4 C839 modification (Shi et al, 2019). METTL17 localizes to mitochondria and associates with the mt-SSU.…”
Section: Mettl15 (M 4 C839)mentioning
confidence: 99%
“…It is also likely that NSUN4 methylates 12S rRNA after the formation of m 4 C839 by METTL15, since inactivation of the latter inhibits NSUN4 ability to modify 12S rRNA [ 10 , 12 , 13 ]. Inactivation of a mitochondrial methyltransferase METTL17, whose target is yet unknown, also leads to a decrease in the efficiency of C841 methylation [ 103 ]. At the same time, methylation of C841 by NSUN4 does not influence an efficiency of m 2 6 A936 and m 2 6 A937 methylation by TFB1M [ 98 ].…”
Section: Common Modified Nucleotides In Mitochondrial and Bacteriamentioning
confidence: 99%
“…Another mitochondrial rRNA methyltransferase, NSUN4, was found to act inefficiently upon inactivation of METTL15 gene [ 10 , 12 , 13 ], which is discussed in a previous section. In turn, activity of METTL15 was found to be reduced upon inactivation of the mitochondrial methyltransferase METTL17 [ 103 ].…”
Section: Common Modified Nucleotides In Mitochondrial and Bacteriamentioning
confidence: 99%